The Babylonian disputation poems with editions of the series of the poplar, palm and vine, the series of the spider, and the story of the poor, forlorn wren - Jiménez, Enrique 1985- (Leiden Boston Brill, 2017)
Â#x80;#x8E;Concordance between Lambertâ#x80;#x99;s and Kienastâ#x80;#x99;s Editionâ#x80;#x8E;Manuscripts and Origins; â#x80;#x8E;Characters and Storyline; â#x80;#x8E;Tradition and Genre; â#x80;#x8E;I.3.b.2. A Sumerian Forerunner?; â#x80;#x8E;I.3.c. Series of Ox and Horse; â#x80;#x8E;I.3.d. The Donkey Disputation; â#x80;#x8E;I.3.e. Nissaba and Wheat; â#x80;#x8E;Chapter I.4. The Place of Disputation Poems within Babylonian Literature; â#x80;#x8E;I.4.a. The Structure of the Disputations; â#x80;#x8E;Prologue; â#x80;#x8E;Disputation Proper; â#x80;#x8E;Adjudication Scene; â#x80;#x8E;I.4.b. The Style of the Disputation Poems; â#x80;#x8E;I.4.b.1. Verse and Style; â#x80;#x8E;I.4.b.2. Language Register; â#x80;#x8E;I.4.c. Literary Quotations
Â#x80;#x8E;I.4.c.1. Specific Allusions and Quotationsâ#x80;#x8E;I.4.c.2. Rebuttal Formula; â#x80;#x8E;I.4.c.3. Speech Introduction Formula; â#x80;#x8E;I.4.c.4. Grievance Formula; â#x80;#x8E;I.4.d. Disputations as Parodies; â#x80;#x8E;I.4.d.1. Parodies in Mesopotamian Literature; â#x80;#x8E;I.4.d.2. Parodies in Graeco-Roman Literature; â#x80;#x8E;I.4.d.3. Parody in Disputation Poems around the World; â#x80;#x8E;I.4.e. Conclusions; â#x80;#x8E;Chapter I.5. Sitz-im-Leben of the Disputation Poems; â#x80;#x8E;I.5.a. Authors and Origins; â#x80;#x8E;I.5.b. Disputation Poems in Libraries; â#x80;#x8E;I.5.c. Disputation Poems in the School; â#x80;#x8E;Chapter I.6. Mesopotamian Disputations in Later Tradition
Â#x80;#x8E;I.6.a. Other Disputations in Antiquityâ#x80;#x8E;I.6.b. Syriac and Arabic Disputation Poems; â#x80;#x8E;I.6.c. Latin and Vernacular Disputations in Medieval Europe; â#x80;#x8E;I.6.d. One or Many Traditions?; â#x80;#x8E;Part II. The Series of the Poplar; â#x80;#x8E;Chapter II. 1. Introduction; â#x80;#x8E;Chapter II. 2. Edition; â#x80;#x8E;II. 2.a. Score; â#x80;#x8E;II. 2.b. Philological Commentary; â#x80;#x8E;II. 2.b.1. On Wind Vanes in Ancient Mesopotamia (on Ic 21â#x80;²); â#x80;#x8E;II. 2.b.2. On Mortise-and-Tenon Joinery in Ancient Mesopotamia (on Ic 35â#x80;²); â#x80;#x8E;Chapter II. 3. Study; â#x80;#x8E;II. 3.a. Origins; â#x80;#x8E;II. 3.b. The Contenders; â#x80;#x8E;II. 3.c. Language; â#x80;#x8E;II. 3.d. Style
Â#x80;#x8E;Chapter V.2. Edition
Â#x80;#x8E;Part III. Palm and Vineâ#x80;#x8E;Chapter III. 1. Introduction; â#x80;#x8E;Chapter III. 2. Edition; â#x80;#x8E;III. 2.a. Score; â#x80;#x8E;III. 2.b. Philological Commentary; â#x80;#x8E;Chapter III. 3. Study; â#x80;#x8E;III. 3.a. Origins; â#x80;#x8E;III. 3.b. Language; â#x80;#x8E;III. 3.c. Style; â#x80;#x8E;III. 3.d. Tradition; â#x80;#x8E;Part IV. The Series of the Spider; â#x80;#x8E;Chapter IV. 1. Introduction; â#x80;#x8E;Chapter IV. 2. Edition; â#x80;#x8E;IV. 2.a. Score; â#x80;#x8E;IV. 2.b. Philological Commentary; â#x80;#x8E;IV. 2.c. A Fragment of a Related Text; â#x80;#x8E;Chapter IV. 3. Study; â#x80;#x8E;IV. 3.a. Origins; â#x80;#x8E;IV. 3.b. The Contenders; â#x80;#x8E;Part V. The Story of the Poor, Forlorn Wren; â#x80;#x8E;Chapter V.1. Introduction
Intro; â#x80;#x8E;Contents; â#x80;#x8E;Acknowledgments; â#x80;#x8E;Abbreviations; â#x80;#x8E;Part I. The Mesopotamian Disputation Poems; â#x80;#x8E;Introduction; â#x80;#x8E;On This Book; â#x80;#x8E;Chapter I.1. Definition of the Corpus; â#x80;#x8E;Chapter I.2. Sumerian Disputation Poems; â#x80;#x8E;Chapter I.3. Akkadian Disputation Poems; â#x80;#x8E;I.3.a. Tamarisk and Palm; â#x80;#x8E;I.3.b. Series of the Fox; â#x80;#x8E;Middle Babylonian Tablets; â#x80;#x8E;Early Neo-Assyrian Tablets; â#x80;#x8E;Neo-Assyrian Tablets; â#x80;#x8E;Neo-/Late Babylonian Tablets; â#x80;#x8E;Uncertain; â#x80;#x8E;Neo-/Late Babylonian School Tablets; â#x80;#x8E;Distribution of Tablets According to Kienastâ#x80;#x99;s Reconstruction
The Babylonian Disputation Poems studies a group of ancient Babylonian poems featuring discussions between animals and trees. It contains editions of several new texts as well as an assessment of the genre and its impact on later traditions of literary disputations
Includes bibliographical references and index
Keywords: Assyro-Babylonian poetry -- History and criticism; LITERARY CRITICISM ; African; Assyro-Babylonian poetry; Criticism, interpretation, etc